WATERMARK DENGAN GABUNGAN STEGANOGRAFI DAN VISIBLE WATERMARKING - Juni Rosmiyati; Teady Matius Surya Mulyana (Universitas Bunda Mulia, 2018)
Images, that are currently circulating on the internet are many, such as advertising images for the promotion of products from a particular brand / institution, the image of the digital image, photographs of the works of famous photographers and many other examples. To identify each image appropriately, it can be added with a special logo or sign that is easily recognizable to the user. But the current advanced technology also supports duplication of the same logo / sign by irresponsible parties. Using the LSB and Grayscale methods, information such as text can be inserted into the watermark image that you want to use. Where there is a combination between the steganography process and the watermark process in one medium so that it can contain information visually and invisible. By using a stegowater application that incorporates stenographic and watermark processes, the user can use it to identify the authenticity of the image being processed, has been through the modification process or not.Keywords: Image, Steganografi, Watermark